Nicorandil Improves Glomerular Injury in Rats With Mesangioproliferative Glomerulonephritis via Inhibition of Proproliferative and Profibrotic Growth Factors - Hirokazu Sudo; Michinori Hirata; Hirotaka Kanada; Keigo Yorozu; Yoshihito Tashiro; Ken-ichi Serizawa; Kenji Yogo; Motoyuki Kataoka; Yoshiyuki Moriguchi; Nobuhiko Ishizuka (Elsevier, 2009)
Recent clinical studies on chronic kidney disease (CKD) reported that renal dysfunction was a critical risk factor for cardiovascular events (CVE), which lead us to reconsider the effect of cardioprotective agents on the kidney. Glomerulonephritis, which is the major cause of CKD, is characterized by mesangial cell proliferation and extracellular matrix deposition. Nicorandil, a therapeutic drug for angina and acute heart failure, have been reported to show antiproliferative activity in mesangial cells. In this study, we first investigated the in vivo effects of nicorandil in anti-Thy1 nephritis rats. In male F344 rats, anti-Thy1 nephritis was induced by the injection of an anti-Thy1 antibody. From three days before induction, nicorandil (10, 30 mg/kg per day) was administered in the drinking water for 12 consecutive days. Anti-Thy1 nephritis resulted in a significant increase in proteinuria and glomerular mesangial cell proliferation. In nephritis rats, nicorandil (30 mg/kg per day) significantly suppressed increase in proteinuria, mesangial cell proliferation (the number of glomerular cell and glomerular area), and renal hypertrophy without affecting blood pressure. Nicorandil significantly prevented the overexpression of type I collagen, fibronectin, transforming growth factor (TGF)-β, and platelet-derived growth factor (PDGF) mRNA. These results suggest that nicorandil may have renoprotective effects in mesangioproliferative glomerulonephritis. Keywords:: nicorandil, anti-Thy1 glomerulonephritis, proteinuria, extracellular matrix, renoprotection